Knowledge of the earthquake in architecture and its impact on the organization of the geography of habitation - Ali Asgharzadeh; Seyed Gholamreza Islami; Iraj Etessam (تحقیقات کاربردی علوم جغرافیایی)
Earthquake and its related phenomenon are often considered as the causes of instability and disorder in engineering and architecture, and have resulted in the destruction of many buildings and urban fabric. Despite this, by changing our attitude to earthquake: by redefining it from problem to potential and from chaos to complex organization, a different layer of this phenomenon can become evident. Earthquake and fault lines can be considered as an organizing factor, which play an important but hidden role in the geography of habitation, e.g. settlement location, urban spatial network, urban development and spatial-structural network of buildings. This article adopts a holistic approach and quantitative-qualitative methodology to identify the role of self-awareness and mental imaging in the complex system of earthquake-qanat-city and its effects on urbanism and architecture in different scales, which has resulted in an earthquake compatible architecture in different periods in the history of Iran and in some contemporary examples too.